IMPLEMENTASI CAPITAL ADEQUACY RATIO DAN HUMAN RESOURCE SLACK DALAM MENGOPTIMALKAN PENERAPAN SUSTAINABLE FINANCE - Selly, Selly Puspita Sari; Sunarmi; Mulyono, Andi (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2023)
Abstract The research objective of this study was used to empirically examine data related to the effect of Capital Adequacy Ratio (CAR) and Human Resource Slack (HRC) on the implementation of sustainable finance implemented from 10 sub-sector sample companies in Islamic banks listed on the IDX for the period 2017- 2020. The analysis used to measure the variables to be examined uses multiple linear regression analysis to test and determine the causal relationship between the independent variables on the implementation of sustainable finance. The results of the research itself show conditions where the Capital Adequacy Ratio has no effect on the implementation of sustainable finance. In addition, a positive effect of Human Resource Slack was also found on the implementation of sustainable finance Keywords capital adequacy ratio; human resource slack; implementation of sustainable finance.